A comparative study of URANS, DDES and DES simulations of Jetstream 31 aircraft near the compressibility limit - Chaudhary, Hrishabh; Ledos, Nicolas; Könözsy, László Z. (Miskolci Egyetemi Kiadó, 2021)
This work presents a comparative study of Unsteady Reynolds–Averaged Navier– Stokes (URANS), Detached Eddy Simulations (DES) and Delayed Detached Eddy Simulations (DDES) turbulence modeling approaches by performing numerical investigation with the ANSYS-FLUENT software package on a full-scale model of the Jetstream 31 aircraft. The lift and drag coefficients obtained from different models are compared with flight test data, wind tunnel data and theoretical estimates. The different turbulence models are also compared with each other on the basis of pressure coefficient distributions and velocity fluctuations along various lines and sections of the aircraft. For the mesh and the conditions presented in this study, the DDES Spalart–Allmaras model gives the best overall results.
Keywords: Jetstream 31; URANS; DES; DDES; Transient Computational Fluid Dynamics